The Maxim of Politeness in The Squid Game Film Series: A Pragmatic Study - Rafif Syauqi Firdaus; Ervina CM Simatupang (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The purpose of this study is to describe the form of speech to the realization of speech acts, the maxim of politeness according to Geoffrey Leech contained in the film of the Squid Game. This type of research is descriptive qualitative research. Data in This research is a description that is used as the object of study; every word, and sentences in an interaction between the actors in the film of the committee as a form of maxim of politeness realization. Collection of the data in this research was carried out by recording technique and note-taking technique. The results of the research on the maxim of politeness in the Squid Game film shows that the number of utterances complies with Leech's maxim of politeness. Politeness contained in the film is also accompanied by the scale of politeness to get the matched analysis. This method is carried out in five stages, namely the tapping technique, then continued with the technique of listening to free, engaging in conversation, then continued with the note-taking technique. After getting the next data, the researcher recorded the results of politeness findings contained in the dialogue, and at the last stage the researcher concludes the results of the overall data. The results showed that of the 30 data (scenes) contained in the film Squid Game and those data that adheres to the principle of politeness Leech consist of tact maxim 8 data, maxim of generosity 3 data, approbation maxim is 10 data, modesty maxim is 6 data and maxim of sympathy 3 data.